Does Fiscal Mechanism Affect the Promotion of Outward Foreign Direct Investment in Green Innovation? - Xiao Lei; Yuanyuan Xie; Xianfeng Chen (Discrete Dynamics in Nature and Society)
This study aims to investigate the driving mechanisms behind outward foreign direct investment (OFDI) on regional green total factor innovation efficiency (GTFIE), focusing specifically on the external fiscal factor perspective. We measured the GTFIE using the super slacks-based model and established a threshold model using financial agglomeration and fiscal decentralization as moderating variables for empirical analysis. The findings indicate that the level of GTFIE in China is relatively low, with an average value of only 0.588 in the sample provinces. It is worth noting that there is a serious imbalance in China’s regional green innovation development. The eastern region has an average GTFIE of 0.886 and is home to nine of the top ten GTFIE provinces. Moreover, regional financial factors exert a substantial moderating impact on the spillover of OFDI. OFDI exhibits a significant dual threshold effect on GTFIE under external fiscal moderation. Specifically, with an increase in the degree of financial agglomeration, the relationship between OFDI and GTFIE changes from being insignificant to a significant positive correlation, with a gradient enhancement. Meanwhile, the relationship between them exhibits an “inverted U-shaped” nonlinear dynamic pattern under fiscal decentralization moderation.